Deadly force and deadly outcome: examining the officer, suspect, and situational characteristics of officer-involved shootings - Jennings, Wesley G. (Deviant behavior, 2020)
Police use-of-force in general, and police use of deadly force in particular, has been at the forefront of national media attention in recent years. Despite this visibility, scholarly attention to the complexities and nuances of the dynamics at play that lead to fatal and non-fatal outcomes for suspects involved in these encounters has been limited. As such, the current study draws from data collected from 2015 to 2018 in the state of Texas to examine the officer-, suspect-, and situational-level correlates and predictors of suspect death resulting from being involved in an officer-involved shooting. Bivariate results suggest that officer race, suspect race, the suspect being armed with a deadly weapon, and the officer responding to a suspicious activity call are significantly associated with suspect death versus being injured in an officer-involved shooting. More rigorous multivariate results reveal that the situational context (i.e., the suspect being armed with a deadly weapon and the incident resulting from a suspicious activity call) is particularly relevant for predicting the lethality of an officer-involved shooting for the suspect. Study limitations and directions for future research are also discussed.